EFFORTS TO PREVENT CROSS-INFECTION IN THE DENTAL CLINIC DURING THE COVID 19 PANDEMIC AT THE PATEK HEALTH CENTER, ACEH JAYA REGENCY - Junita, Putri; Raisah, Putri; Zahara, Hafni (Transpublika Publisher, 2023)
In the context of healthcare, the principle of prevention plays an important role in minimizing the risk of infection. Infections can be caused by various factors, including accidents such as being pricked by sharp instruments, contamination from unsterilized hands, or respiratory transmission. Therefore, infection control becomes a key strategy for dentists to avoid the risk of cross-infection that could potentially harm patients and medical staff. The role of dental nurses in avoiding or preventing cross-infection cannot be ignored, especially in pandemic situations such as Covid-19. Sterilization of dental medical devices is a crucial step that must be carried out appropriately and correctly to ensure the safety of patients and medical staff. This study aims to explore the understanding of ways to prevent cross-infection during the Covid-19 pandemic, especially in the context of the dental clinic at the Patek Health Center, Aceh Jaya Regency. The research method used was an analytic survey with a cross-sectional study approach, where data were collected simultaneously at one point in time. The study population consisted of two dental nurses and patients visiting the dental clinic. The sample taken was the total population available. Data collection was carried out using a questionnaire to measure the level of knowledge and a checklist sheet to record the actions taken.